Menumbuhkan Jiwa Berwirausaha Melalui Pendidikan Kewirausahaan Bagi Generasi Muda - Farwati, Sizka; Santosa, Sedya (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2023)
This research aims to overcome these problems through a literature study that produces descriptive data related to strategies to foster the entrepreneurial spirit through entrepreneurship education for the younger generation. Data collection techniques are obtained from various references in the form of books, articles, relevant literature, and other records. The results showed that entrepreneurship education programs can reduce unemployment and form competitive individuals. Entrepreneurship education involves character building, understanding, and skills as an entrepreneur. Entrepreneurship education plays an important role in building and developing entrepreneurship. The main role of entrepreneurship education includes education about, through and for enterprises. Strategies for fostering entrepreneurial spirit in schools involve preparingeducated personnel and educators who have an entrepreneurial spirit. Entrepreneurship has an important role to play in reforming the education system to encourage creativity and innovation in the younger generation. Educational institutions play a greater role in fostering the entrepreneurial spirit.